Elevating Students’ Reading Comprehension Using Story Maps - Rengur , Zul Aini; Fatima; Mansur, Nurfauziah; Prisna Aswarita Putri; Zulfikri (Samudra Publisher, 2026)
This research investigated the effectiveness of Story Maps compared to conventional media in elevating students’ reading comprehension. Employing a quasi-experimental design, the study involved the experimental group and control group, comprising TBI students of Datokarama Palu State Islamic University. The independent variable was the implementation of Story Maps, while the dependent variable was the students' reading comprehension levels. Data were collected through pre-test and post-test and subsequently analyzed using Analysis of Covariance (ANCOVA). The findings demonstrate that Story Maps significantly more effective than conventional media in improving reading comprehension. The results of the LSD (Least Significant Difference) test yielded a mean difference of 0.191 with a significance value (p=0.00), which is well below the 0.05 threshold. Furthermore, the positive mean difference in the LSD test indicates that Story Maps is the most effective tool among the tested media for teaching reading comprehension. These results suggest that visualizing narrative structures through Story Maps effectively elevates students' ability to process and understand texts.